The Northern Research Forum, a case study for High Northern cooperation. - Margrét, Cela (Arctic Portal, 2011)
Margret Cela, University of Lapland, Finland / Iceland, talks here in the NRF 6th open assembly in Hveragerði, Iceland, in September of 2011. Please click on the link above to see the video.